The Effect of Maternal Anemia on Low Birth Weight: A Systematic Review And Meta Analysis - Azizah, Fara Khansa; Retno Dewi, Yulia Lanti; Murti, Bhisma (Journal of Maternal and Child Health, 2022)
Background: Low birth weight (LBW) is a risk factor for morbidity and mortality in infants. Several previous studies have suggested that maternal anemia has an effect on several adverse perinatal outcomes, including low birth weight. The purpose of this study was to investigate the effect of anemia in pregnant women on the incidence of low birth weight. Subjects and Method: This study is a systematic review and meta-analysis done by searching for articles published by the online database PubMed, ResearchGate, Science Direct, Google Scholar and EBSCO in 2016 to 2021. Population: pregnant women, intervention: anemia, comparison: no anemia, and outcome: low birth weight). Data analysis using RevMan software version 5.3. Results: Pregnant women who experience anemia during their pregnancy are at risk of giving birth to babies with low birth weight compared to mothers who are not anemic (OR= 3.42; 95% CI= 1.85-6.34; p < 0.001). Conclusion: Mothers who experience anemia during pregnancy is one of the risk factors for the occurrence of babies with low birth weight.